THE ROAD TO YOURSELF: A STUDY OF PRESERVING IDENTITY AND OVERCOMING THE TRAUMATIC EXPERIENCE OF WAR IN ANDRII LYUBKA’S COLLECTION "WAR FROM THE BACK SIDE" - Haikova, Anna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The aim of the article is to reveal the anthropological and ethical aspects of the existence of an individual in wartime through the prism of Andriy Lyubka’s essays. Research methodology. The study uses a comprehensive approach based on the principles of hermeneutics and anthropological analysis. The theoretical basis is formed by works on the psychology of trauma and philosophical concepts of existentialism. Elements of trauma studies (the works of Katie Caruth, Dora Lauby, Shoshanna Felman, Dominic La Capra) are also involved, which help to analyze the mechanisms of psychological adaptation of civilian heroes to the conditions of the front. The relevance of the study lies in identifying and systematizing the ways of preserving identity, which the author describes and applies. The object of the study is the texts of the collection “War from the Back Side”, and the subject is the ethical and existential dimensions of human existence in the conditions of war reality and their artistic realization in the texts of Andriy Lyubka’s essays. Search results. The article analyzes the collection of essays by Andriy Lyubka “War from the Back Side” as an artistic study of changes in Ukrainian society as a result of a full-scale invasion. The author’s specifics of the perception and depiction of the transformation of civilian roles into military ones, the ethical aspects of the interaction between the front and the rear are clarified. The specifics of the artistic understanding of war in the collection of essays by Andriy Lyubka “War from the Back Side” are also revealed by analyzing the role of key metaphors of the work. The relevance of the article is due to the need for a scientific analysis of the “literature of testimony” and ways of preserving identity in conditions of existential threat. It is proven that the center of the author’s artistic world is the protection of the "human in man" as the highest act of resistance. Attention is also focused on the deconstruction of the key metaphors of the work - "draft", "bridge" and "Macondo", which mark the existential state of the "transit country". It is proven that the concept of "life on the bridge" reflects the psychological insecurity of the individual, torn from a stable chronotope. In the context of military anthropology, the phenomenon of the "civilian army" is analyzed, where volunteering and military service appear as acts of conscious choice of an intellectual. Special emphasis is placed on the sacralization of everyday rituals (making coffee, reading books), which function as mechanisms of psychological protection and preservation of identity. Among the studies that focus on the cultural context of the experience of trauma, as well as strategies that help to tell about trauma in fiction, are the works of Irene Visser "Decolonization. Trauma. Theory: Retrospective and Perspectives. Humanity” (2015) and “Trauma in a Non-Western Context” (2018), E. Santner “History Beyond the Pleasure Principle: Reflections on the Representation of Trauma” (2009). Nowadays, the active assimilation of the trauma studies methodology by postcolonial studies continues [3, 4 p. 65, 81]. The ethical discourse of the article covers the consideration of conflict zones between the front and the rear, as well as the critical reception of the Western perception of the Ukrainian experience as an “object of pity”. It is substantiated that the author creates a “narrative of resilience”, where the highest form of resistance is the right of a person to remain himself – “impractical”, reflective and free – despite the dehumanizing impact of war. It is proven that in the author’s texts, private space, habitual social practices and appeals to world cultural archetypes become the foundation for overcoming traumatic experience and forming a “narrative of resilience”.